Characterization of biomechanical parameters during stair ascent - Kuriki, Heloyse [UNESP]; Azevedo, Fábio [UNESP]; Alves, Neri [UNESP] (Elsevier, 2012)
Stair climbing is a functional activity often cited as main complaint by patients with orthopedic – as patellofemoral pain syndrome – or neurologic alterations. Moreover, the stair climbing is usually used as therapeutic resource. However, few studies have been conducted to characterize the movement during the ascent or descent of stairs and these studies concluded that the high variability of the data could not confirm the results [Yu, 1997] . In this way, this study aimed to verify which parameters show less variation and so, are more appropriate to characterize the stair climbing.